La trasmisión de las constituciones de Don Remondo de 1261. Su nueva promulgación en 1411. - Belmonte Fernández, Diego (Scrineum, 2017)
This paper aims at investigating the concept of originality and how it can be applied today to the surviving different versions of a fundamental document in the history of Seville’s Church: the Constituciones (Statutes) of Don Remondo’s, first archbishop of the diocese, consecrated after the Christian reconquest, that promulgated them in 1261. The Constitutiones laid the legal and economic foundations of the Sevillian restored Church and established its legal pillars, that survived until the 19th century. The first version of these statutes is not kept anymore but a number of copies of them were preserved in different pragmatic codices. Did a document translated and updated in 1411 have the same legality and authenticity as its model? It seemed so, as this new version is placed in one of the codices of greatest value to the institution at the time it was created. To conclude, the complete edition of this re-enactment of the text is provided.